Interactive documentary and its limited opportunities to persuade. (December 2017) - Forceville, Charles
Abstract: John Grierson's classic definition of documentary as the "creative treatment of actuality" emphasizes both the genre's indexical link to reality and the maker's perspective on this reality. In recent times, a substantial number of so-called "interactive" documentaries has seen the light of day. In this paper, one dimension of such online documentaries, namely the freedom of users to access content via different paths of navigation as well as to skip material, is discussed from the perspective that a documentary, in a necessarily subjective way, attempts to convince the viewer of something. Interactivity limits the maker's opportunities to do so.